Sensitivitas Keibuan Pada Perempuan Korban Kekerasan dalam Rumah Tangga - Bellani, Gestadela; Nu'man, Thobagus Moh (Universitas Islam Indonesia, 2014)
The main aim of this study was to understand how maternal sensitivity of domestic violence victim woman. This study also identify the factors of the maternal sensitivity. This study enganged two subjects that has been experienced getting domestic violence. Result ofthis studyfounded that maternal sensitivity of the subjects could be categorized into two levels; weak and strong maternal sensitivity. Strong maternal sensitivity can be seen by accepting the baby, cooperative with the baby, physical contact, emphaty, nurturance, the way of mother in fulfilling the baby's need when mother does not have money, hope and wish that still thinks about the baby. Meanwhile, the weak maternal sensitivity shown with rejecting of the baby present, neglecting, interfering, and agresivity. The weak maternal sensitivity effects on insecure attachment. Strong maternal sensitivity effects on secure attachment. The factors correlated with the maternal sensitivity are social support, baby's behavior, intensity of mother to meet the baby, the characteristic and condition of the mother, and value of children. In this study founded that social support is used by mothers as coping and helping mother to fulfill the baby's needs.Key words: maternal sensitivity, domestic violence